Analysis of Factors Contributing to Elementary Students’ Difficulties in Understanding Fractions - Malau, Angel Angreni; Abrara, Deya Yuna Rusydiana; Sinaga, Juni Arta; Sianturi, Tiur Claresya; Sembiring, Icha Florensia (Teaching, Learning, and Development, 2025)
This study uses a literature analysis method to examine the factors causing learning difficulties in fraction concepts in Elementary Schools. The analysis was conducted on 11 research articles discussing the topic. The results of the analysis indicate that learning difficulties in fractions are caused by internal factors such as lack of conceptual understanding, low memory, and low interest in learning. External factors such as lack of use of learning media and a less conducive learning atmosphere also contribute to these difficulties. The implications of these learning difficulties in fractions are very significant, because they can hinder students' understanding of more complex mathematics material at the next level. Effective learning strategies to overcome learning difficulties in fractions include introducing concepts contextually, using various visual representations, implementing collaborative learning models, making connections with other mathematical concepts, providing varied practice questions, using concrete learning media, working with parents, and conducting tutoring. This study is expected to contribute to educators and researchers in understanding the factors causing learning difficulties in fractions in Elementary Schools and designing effective learning strategies to overcome them.